Analysis and assessment of the hazardous geological processes influence on the marine pipelines - IVANIK, O.; SHEVCHUK, V.; HORBAN, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Geological hazards distorting the balance in the system "geological environment–pipeline" in the offshore zones are defined. It is proved that the loads and influences depend on the pipe location on the sea bottom. They characterized by the elastic-plastic strain of the soil and hydrodynamic forces. Calculations of these effects are belong to the theory of stability of secluded cylindrical shell.